PELAKSANAAN KEGIATAN PELAYANAN KELILING PEREKAMAN E-KTP DI KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Siti Zubaidah; Rusdi Laili; Dian Kristiawan (JURNAL ILMIAH ILMU ADMINISTRASI, 2020)
This study discusses the implementation of Mobile Recording E-Identity Card Service Activities in Tanjung Lago District, One of which supports the implementation of the E-Identity Card is a printing press. The regions do not yet have permission to choose their own E-Identity Card because the current authority is still at the Center. On the basis of the above problems, a special government apparatus in Tanjung Lago Subdistrict, Banyuasin District, did a recording of the E-Identity Card to help and facilitate the community in the process. This study uses a qualitative method with observation techniques and direct interviews with informants. The conclusion of this study is that there are still people who do not have an E-Identity Card because the people in Tanjung Lago District are happy to record e-ID Card and related printing machines that are still at the center and there are still responses to the government that are less friendly from the government apparatus in Tanjung District, For this reason, infrastructure facilities to support the e-ID card recording process in Tanjung Lago Subdistrict are provided by the central government.